Hemostasis features in pregnant women with preeclampsia for cesarean section under general and epidural anesthesia - V. P. Muzychenko; R. V. Shadrin (Кубанский научный медицинский вестник, 2014)
The aim of our study is to explore the hemostatic system features in pregnant women with preeclampsia undergoing operative delivery under general and regional anesthesia. We have found that the most common disorders of hemostasis in this category of patients is hemodilution coagulopathy; in patients with severe preeclampsia degree of incidence of chronic DIC was significantly higher than in the other groups that should be considered when assessing the dynamics of patients condition and choice of anesthetic. Shown that the duration and nature of the cure of coagulopathy associated with preeclampsia, depends on the anesthetic method. The use of long-term epidural anesthesia allows you to more quickly and with less need to use drugs to stop blood available hemostatic disorders.